Perforated duodenum with hemorrhage while on V-V ECMO: Diagnostic challenge - Arwa Rifaii; Ahmad Osta; Samir Akel; Jana Assy; Issam El Rassi (Elsevier, 2021)
ECMO and cannula-related complications remain a concern in critical care, and may conceal serious unrelated underlying medical or surgical problems. A 22 month-old male patient was put on veno-venous ECMO for H1N1 infection using jugular and femoral cannulas. Iliac vein perforation by the cannula was suspected following abdominal distention and fresh blood in the abdomen. Emergent laparotomy unexpectedly revealed a perforated duodenum, which was primarily repaired. This is the first reported case of a duodenal perforation in a child on ECMO. With increasing use of ECMO, more attention should be given to rare complications related to the underlying diseases.